Going remote during COVID-19 pandemic: effects of problem based learning towards improving students' critical thinking and problem-solving skills - Low, Kah Choon; Mohamad, Siti Syuhadah; Chong, Say Lee (2020)
COVID-19 pandemic spreading all around the world, the higher learning institutions were forced to shut or limit the person in contact to control the spread of diseases. Under this circumstance, remote learning that emphasizer learning via online setting embraced in higher education to replace the physical classroom during the pandemic time. This study designed a single Problem-Based Learning (PBL) module using remote learning to examine the students experience in PBL, and to what extent the PBL module helps students to improve their critical thinking and problem-solving skills. The remote learning PBL module conducted using reflection method to assess the students' experiences in PBL learning. On the other hand, a set of survey questionnaires was distributed to 34 undergraduate students to gather the responses for the assessment of critical thinking and problem solving skills. This study employed both quantitative and qualitative analysis to investigate the students' critical thinking, problem-solving skills and their experience in remote learning PBL. Using paired sample t-test to test the difference between pre-and-post- remote learning PBL class, results indicated that there was a significant improvement of students' critical thinking and problem-solving skills after remote learning PBL class. On the other hand, thematic analysis on students' feedback on remote learning PBL class- first, second, and third meeting, indicated that students gradually improved their critical thinking and problem-solving skills. Although students implied positive feedback on the class, however, some of them were facing difficulties ~n understanding the module or physical disruptions that distract their learning. The findings gave insights for the lecturers to design a suitable learning course during the pandemic time. Moreover, the findings highlighted challenges that gave insights for tbe lecturers to look at the students' feedback from time to time to improve the learning mechanisms and to create a better learning environment.